Wednesday

April 16, 2014

April 16, 2014

Posted by **how** on Thursday, August 8, 2013 at 12:01pm.

- math -
**Steve**, Thursday, August 8, 2013 at 12:13pm3(b-2) / 3(b^2-4)

= 3(b-2) / 3(b-2)(b+2)

= 1/(b+2)

**Related Questions**

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

algebra - a^6b^8-a^4b^3+a^3b^5-a^3b^3 ???

Math - Simplify the following (6b-2)(6b+2)+4(b^2-3b) Find the factors of the ...

Math - Use the elimination method to solve a+6b=14 and a+3b=5

math - Can someone show me the steps necessary to simplify the expression by ...

Algebra 12345!!! - (5a^3b^4)2 would it be: 10a^6b^8 five squared is 25, and ...

algebra - siplify the expression 1/4(6b +2) - 2/3(3b-2)

math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...

Math - Which of the flowing formulas a correct rewriting of the formula a=6b - ...

algebra - combine and reduce 6b/3a + b/a = answer 3b/a